PRESCRIPTIONS AND SCHEDULING OF ENDOVENOUS MEDICATIONS IN PEDIATRICS: DESCRIPTIVE STUDY. - de Oliveira Mota, Rafaela; Costa, Cristina Oliveira da; de Souza Brito, Eva Anny Welly; de Souza, Thais Lima Vieira; Sandoval, Lilia Jannet Saldarriaga; Custódio, Ires Lopes; Lima, Francisca Elisângela Teixeira (Revista Mineira de Enfermagem, 2021)
Objectives: to analyze the prescriptions and scheduling of intravenous medications for hospitalized children and adolescents, following the recommendations of the Safety Protocol in the Prescription, Use, and Administration of Medicines. Methods: descriptive, documentary study, with analysis of 352 prescriptions for intravenous medications in pediatric inpatient units. The age range of the children was 29 days up to 16 years old. Data collection took place from August to November 2017. A checklist-type instrument was used. The analysis was performed using descriptive statistics, in compliance with ethical precepts. Results: we found that the performance was satisfactory concerning the prescriptions and followed the recommendations of the Ministry of Health of Brazil. The essential items in medication prescriptions had the following incidences: date (98%), generic name (95.2%), concentration (98.6%), dose (99.7%), route of administration (95.7% ), dosage (98.9%), guidelines (87.5%), physician's signature (99.1%), medical stamp (97.7%), nurse's signature (93.2%) and nurse's stamp (84.7%). In the 352 prescriptions, 1,069 medications were analyzed, of which 1,059 (99.06%) presented satisfactory data regarding the verification of intravenous medications. Conclusions: most of the prescription items were satisfactory; however, some items were considered unsatisfactory, with actions not performed correctly.